Journey to the center of the earth - Verne, Jules ([S.l.] : Dover Publications, 1993)
A pioneer in the genre of science fiction writing, Jules Verne possessed an uncanny ability to imagine--often with startling accuracy $1 (Bthe future possibilities of science. In this classic novel, first published in 1864, the author introduces readers to Otto Lidenbrock, a professor of geology who ventures into a fantastical world within an extinct Icelandic volcano. Verne's vivid imagination and masterful storytelling ability has made this book a popular choice among readers for more than 140 yearss